Biotechnological applications of archaeal enzymes from extreme environments - Ma. Ángeles Cabrera; Jenny M. Blamey (Biological Research, 2018)
Abstract To date, many industrial processes are performed using chemical compounds, which are harmful to nature. An alternative to overcome this problem is biocatalysis, which uses whole cells or enzymes to carry out chemical reactions in an environmentally friendly manner. Enzymes can be used as biocatalyst in food and feed, pharmaceutical, textile, detergent and beverage industries, among others. Since industrial processes require harsh reaction conditions to be performed, these enzymes must possess several characteristics that make them suitable for this purpose. Currently the best option is to use enzymes from extremophilic microorganisms, particularly archaea because of their special characteristics, such as stability to elevated temperatures, extremes of pH, organic solvents, and high ionic strength. Extremozymes, are being used in biotechnological industry and improved through modern technologies, such as protein engineering for best performance. Despite the wide distribution of archaea, exist only few reports about these microorganisms isolated from Antarctica and very little is known about thermophilic or hyperthermophilic archaeal enzymes particularly from Antarctica. This review summarizes current knowledge of archaeal enzymes with biotechnological applications, including two extremozymes from Antarctic archaea with potential industrial use, which are being studied in our laboratory. Both enzymes have been discovered through conventional screening and genome sequencing, respectively.